The relationship between the Translator´s Professional Role and the judges final verdicts at Criminal Courts in Quito, June 2003 February 10th 2009 - Villota Miño, Patricio Rodrigo (2012)
Translators have a fundamental role at Criminal Courts located at Oe-109 Ramirez Davalos St. in Quito, Ecuador. The three Courtrooms housed public hearings where translators have three different roles upon the case of judgement at its headquarters. The first role of the translator is to reproduce orally what is being said by the three procedural parties involved in the process: Judge, defendant, and prosecutor using consecutive translation techniques. The second role of the translator at Criminal Courts of Quito is to hand in translations assigned by the Office of Foreign Affairs, using written translation techniques, which are to be explained at the report; Finally the third role the translator at Criminal Courts of Quito is to execute sight translation as any procedural part petition takes place within the process with the consent of the Judge. Judges´ final verdicts, on the other hand, have not only to be concrete but reliable, they do not always accept translations as evidence since these are considered optional, and depends on the judge whether to accept them. If there is confusion in the translation, a second translation is effected by another translator and if any doubts are created at this point, the judge is to appoint a diriment translator, whose version will be final and optional. The researcher mentions that translators could have helped producing workable evidences to punish, rehabilitate, or absolve accused inmates if proper documents would be presented during trials at Criminal Courts of Quito-Ecuador providing light to judges at different instances of the process as required by Ecuadorian current Criminal Law Code...